Post‐sample aperture for low background diffraction experiments at X‐ray free‐electron lasers. (16th October 2017) - Wiedorn, Max O.; Awel, Salah; Morgan, Andrew J.; Barthelmess, Miriam; Bean, Richard; Beyerlein, Kenneth R.; Chavas, Leonard M. G.; Eckerskorn, Niko; Fleckenstein, Holger; Heymann, Michael; Horke, Daniel A.; Knoška, Juraj; et al.
Abstract : Diffraction experiments with weakly scattering samples often suffer from a low signal‐to‐noise ratio due to unwanted background scatter. Improving the signal‐to‐noise ratio for single‐particle imaging experiments is particularly important as the diffraction signal is very weak. Here, a simple way to minimize the background scattering by placing an aperture downstream of the sample is demonstrated. Abstract : The success of diffraction experiments from weakly scattering samples strongly depends on achieving an optimal signal‐to‐noise ratio. This is particularly important in single‐particle imaging experiments where diffraction signals are typically very weak and the experiments are often accompanied by significant background scattering. A simple way to tremendously reduce background scattering by placing an aperture downstream of the sample has been developed and its application in a single‐particle X‐ray imaging experiment at FLASH is demonstrated. Using the concept of a post‐sample aperture it was possible to reduce the background scattering levels by two orders of magnitude.